Impact of Salicylic Acid and PGPR on the Drought Tolerance and Phytoremediation Potential of Helianthus annus - Khan, Naeem; Zandi, Peiman; Ali, Shahid; Mehmood, Asif; Adnan Shahid, Muhammad; Yang, Jianjun (Frontiers in Microbiology, 2018)
The present study was aimed to isolate and characterize plant growth promoting rhizobacteria (PGPR) from the rhizosphere of rainfed area (Karak) in Pakistan. The influence of isolated rhizobacteria, in association with salicylic acid (SA), physiological attributes, drought tolerance potential and phytoremediation in drought-stressed sunflower exposed was investigated. The isolated bacteria were named as P1 and P2 and characterized on the basis of colony morphology, and biochemical traits. Both PGPR P1 and P2 were identified on the basis of 16S-rRNA gene sequencing as Planomicrobium chinense strain P1 (Accession No. MF616408) and Bacillus cereus strain P2 (Accession No. MF616406). The fresh cultures (24 h old) of isolates were used to soak the seeds pre-sowing. Salicylic acid (SA) was foliar applied at three-leaf-stage. Likewise, the 30-days-old seedlings (three leaf stage) was exposed to drought stress. Drought stress was imposed to 30 days old plants (three ‐leaf stage) by withholding water supply for the next 15 days until the soil water content reached 10%. The PGPR and/or SA treatment resulted in significant accumulation of Cd (84%), Pb (66%) and Ni (65%) in the rhizosphere. Plant growth promoting rhizobacteria also induced accumulation of Cd and Ni in plant shoot. Combined treatment of PGPR and SA increased the Cu (21%), Co (11%) and Zn (8%) accumulation but decreased (12%) the Fe accumulation as compared to coinoculation of PGPR P1 and P2. Inoculation of plants with PGPR significantly increased shoot length (60%), root length (68%), root fresh (61%), and dry (63%) biomass under water stress. The inoculated plants had increased chlorophyll (67%),carotenoid (70%), leaf protein (64%), sugar (64%) and phenolic (62%) contents while lower leaf proline (62%) content, malondialdehyde (MDA) (64%) and antioxidant enzymes (67%) which suggest their role in drought tolerance. It is concluded that integrative use of PGPR in combination with SA found to be an efficacious strategy to improve the phytoremediation of heavy metals and plant growth under stressed conditions particularly under water deficient conditions.